The Human Side of Scaling: How Employees experience ‘Growing Pains’ in a Scaling Fintech Company - Schweer,Luca Sophie; Schopf,Sophia Fidelis (2025)
This thesis contributes to scaling literature by offering an employee-centred view of scaling processes and enriching Picken’s (2017a) model with insights from employee experiences. Further, it critically analyses the ‘growing pains’ metaphor and highlights how it shapes and can obscure perceptions of workplace change.
Keywords: Organisational Scaling; Growing Pains; Employee Experience; Metaphor